PRELIMINARY EXPERIENCE OF THE AORTO-FEMORAL SHUNTING USING THE DA VINCI SURGICAL SYSTEM - V. N. Pavlov; V. V. Plechev; R. I. Safiullin; V. Sh. Ishmetov; M. Sh. Kashaev; P. V. Ignatenko; A. N. Arhipov; A. A. Rabtsun; R. F. Safin; A. E. Pushkareva; S. I. Blagodarov (Креативная хирургия и онкология, 2018)
Introduction. Robot surgery is one of the most high-demand and dynamic developing realms of medicine. It is widely used in urology, proctology, thoracic, cardiovascular surgery and gynecology. In February 2018 a robot surgery centre opened in Volga Federal District of the Russian Federation based on the clinic of the Bashkir State Medical University (city of Ufa).Materials and methods. The present paper demonstrates the first successful robot-assisted vascular operations within a master-class called "Aorto-Femoral Shunting with the use of robot-assisted surgical system Da Vinci".Results. Exemplified with three operations: two linear aorto-femoral shunting and lumbar sympathectomy demonstrate technical peculiarities and advantages of robot-assisted vascular surgery. The findings show positive short-term results of the performed surgical interference that combine minimal injury and blood loss which help to reduce hospital stay in an intensive therapy department and intestinal distention duration. These clinical effects enabled to provide early activization of patients and possibility to adequately correct nutritional status with enteral feeding. The above-mentioned advantages eventually resulted in reduction of post-operation stay of patients in in-patient department and of cost of treatment.Conclusion. Robot-assisted surgical system Da Vinci being the most cutting-edge in the realm of endoscopic surgery, enables to carry out operational interference with minimal blood loss and injury of tissues which helps to reduce postoperation and recovery periods.